(untitled) (Research, Society and Development, 2024)
Introduction: Acute lymphoblastic leukemia (ALL) is the most common malignant hematological disease in the pediatric community, highlighting the importance of ongoing investigation into its risk factors to improve early diagnosis and prognosis rates. Objective: This study aims to highlight the risk factors of childhood ALL and emphasize the importance of implementing health strategies to mitigate them. Methodology: This is an integrative systematic literature review, utilizing data from the PubMed platform, conducted in 2024, with the MeSH descriptors “Precursor Cell Lymphoblastic Leukemia-Lymphoma,” “child,” and “risk factors,” combined with the Boolean operator AND. Furthermore, the descriptor “treatment” was added with the operator NOT, resulting in 60 articles, which were filtered by “free full text” and “last five years.” After applying the inclusion and exclusion criteria, 23 articles were selected. Results: Identified risk factors include exposure to carcinogens, such as pesticides and toxic gases (benzene), proximity to magnetic fields, and artificial light. Maternal health during pregnancy is also related to risk, including maternal infections and exposure to high temperatures. Immune response and genetic polymorphisms, especially in Hispanic children, also contribute to the etiopathogenesis of ALL. Conclusion: Childhood ALL remains prevalent, and although therapeutic advances have raised survival rates to 90%, environmental and genetic factors still influence its incidence. Future research should integrate environmental prevention and genomic advances for a better understanding and control of ALL.